Canine Tonsillar Polyps: Characteristics, Classification, and Review of the Pathogenesis. Issue 1 (January 2021) - Molín, Jéssica; Vilafranca, Miquel; Suárez-Bonnet, Alejandro; Altimira, Jaume; Ramírez, Gustavo A.
Canine tonsillar polyps are uncommon. We describe 14 tonsillar polyps in dogs and review their classification and pathogenesis. All dogs were adult (3–13 years old). Females (10/14) were more affected than males (4/14). Most of the lesions were asymptomatic (10/14). All lesions were unilateral, pedunculated (9/14), or sessile (5/14), with a smooth (12/14) or papillary/verrucous surface (2/14). Histologically, polyps consisted of benign proliferation of lymphatic vessels, blood vessels, fibrous tissue, and lymphoid tissue in variable proportions, with occasional adipose tissue (4/14). According to the main stromal components, polyps were categorized as lymphangiomatous (5/14), lymphangiolipomatous (2/14), lymphangiofibromatous (2/14), angiofibromatous (1/14), angiofibrolipomatous (1/14), lymphoid (2/14), and myxomatous (1/14). As the pathogenesis of these polyps remains unclear, we propose to replace the term inflammatory tonsillar polyp by a morphological diagnosis based on the stromal characteristics of the lesions. Simple surgical excision was curative in the 9 cases with available follow-up information.